The Effectiveness of the Experiential Learning Method in Classical Guidance to Enhance Students' Understanding of Emotion Regulation Material - Agustian , Agustian; Achmad, Listian Indriyani; Muktiali, Saiful; Juariah, Siti (Proceeding International Pelita Bangsa, 2023)
This study is a qualitative research using a descriptive method, aiming to determine the effectiveness of applying the Experiential Learning Method in classical guidance to enhance students' understanding of emotional regulation material based on students' perceptions. Effectiveness is determined by the alignment between the results obtained and the learning objectives. The research was conducted in the classroom of SD Islam Salman Al Farisi Bekasi, with 40 participants as the research subjects. Data collection was carried out using a questionnaire form, triangulated with interviews and document analysis of student assignments. The results indicate that, according to students' perceptions, the application of the Experiential Learning Method in learning is effective, as shown by the achievement of learning outcomes. The implementation of the Experiential Learning Method also increases motivation, provides understanding and hands-on experience in emotional regulation, and enhances skills in expressing emotions.